Integrating Tentara Genie Pelajar Values into Local-History-Based Social Studies: A Qualitative Case Study of Character Education in an Indonesian Junior Secondary School - Ririn Wahyuni; Muhammad Hanif; Ibadullah Malawi; Muhammad Rifa'i (AL-ISHLAH: Jurnal Pendidikan, 2026)
Character education in Social Studies is often constrained by textbook-centered instruction, limiting the incorporation of local heritage as a meaningful context for value formation. This study investigates the integration of Tentara Genie Pelajar (TGP) struggle values into local-history-based learning to enhance students’ character development. A qualitative case study design, supported by descriptive statistics, was conducted at SMP Negeri 4 Pare involving four Social Studies teachers and 140 seventh-grade students. Data were collected through in-depth interviews, participatory observations, and Likert-scale questionnaires. The analysis employed thematic techniques for qualitative data and descriptive percentages for quantitative responses. The integration of TGP local history positively influenced students’ character development. Approximately 78% of students demonstrated improved understanding of struggle values, 72% exhibited increased cooperative behavior, and 69% showed strengthened nationalism. Key supporting factors included the availability of authentic historical artifacts and high levels of student engagement. However, challenges were identified, particularly the lack of structured instructional modules and limited teacher training in heritage-based pedagogy. The findings highlight the effectiveness of contextualizing Social Studies learning through local history to foster character education. Integrating heritage-based content not only enhances cognitive understanding but also promotes affective and social competencies. Despite implementation challenges, the study provides practical insights for educators and underscores the need for systematic support, including teacher training and curriculum development. Future research should examine comparative contexts and long-term impacts to optimize the sustainability of local-history-based character education.